Analysis of family takaful and life insurance demand in Kelantan, Malaysia - Nurul Amirah Mohd Mazlan; Intan Suzila Mod Resedi; Maisarah Amira Mustafa; Mohammad Alif Nasuha Rofidi (2022)
Family Takaful plays an important role in maintaining the financial well -being of all communities and helping people improve their standard of living. The purpose of this study was to investigate the relationship between the factors and the demand for Family Takaful. For this purpose, data were collected from residents of Kelantan and the sample consisted of 384 respondents. The sampling method used in this study is a probability sampling technique and the questionnaire form is distributed through Google form. The findings obtained from this study indicate that religious affiliation, income level, reputation and image and marketing and advertising are factors that have a significant relationship with Family Takaful demand. However this study has some limitations and there are some suggestions put forward for future studies.